(untitled) (Cambridge, UK,New York, 2003)
In mid-May 1997, a financial crisis erupted in Asia after an attack by private investors on the baht, the Thai currency. The crisis spread quickly across the region, where investor confidence plummeted, resulting in massive capital outflows, stock market collapses, high unemployment, and even insurrection. The Asian 'economic miracle' that had stimulated so much awe and even dread, now invoked pity and apprehension in greater measure. The contributors to this volume investigated change in the innovation and production systems of Asian states in response to economic and political upheaval. They conducted empirical studies of several regional industries - autos, semiconductors, and hard disk drives - and seven different national economies: China, Malaysia, Japan, Singapore, South Korea, Thailand, and Taiwan. In the face of crisis and global competition, the Asian states superimposed change at the margins, seeking unique technohybrid solutions to build capabilities to compete in local, regional, and even global markets.
Keywords: Technological innovations,Technological innovations,Microelectronics industry,Microelectronics industry,Đổi mới công nghệ,Đổi mới công nghệ,Công nghiệp vi điện tử,Công nghiệp vi điện tử; Economic aspects,Economic aspects,Khía cạnh kinh tế,Khía cạnh kinh tế; East Asia,Southeast Asia,East Asia,Southeast Asia,Đông Á,Đông Nam Á,Đông Á,Đông Nam Á